Hydrothermal Synthesis and Characterization of an Apatite-Type Lanthanum Silicate Ceramic for Solid Oxide Fuel Cell Electrolyte Applications - Jena P.; Patro P.K.; Sinha A.; Lenka R.K.; Singh A.K.; Mahata T.; Sinha P.K. (My University, 2025)
Apatite-type lanthanum silicate (La10Si6O27; LS) nanopowders are synthesized using a hydrothermal process and used for the electrolyte applications in solid oxide fuel cells (SOFCs). The synthesized nanopowders are characterized by Rietveld refinement of the X-ray diffraction (XRD) data, SEM–energy-dispersive X-ray spectroscopy (EDS), TEM, and dialotometry. The prepared nanopowders can be sintered to near theoretical density at sintering temperature of 1500 °C. Reactivity studies between the synthesized La10Si6O27 material and cathode materials such as La0.6Sr0.4Co0.2Fe0.8O3−δ (LSCF), Nd2NiO4 (NNO), and Pr2NiO4 (PNO), are carried out by XRD analysis revealing that they do not react. Symmetric cells are fabricated and characterized electrochemically. The area specific resistances for LSCF, NNO, PNO, and PNO-LS (1:1 (wt %)) measured at 900 οC, are 100, 2.2, 1.8, and 0.5 Ω cm2, respectively. EDS analysis shows that interdiffusion of cations at the cathode–electrolyte interface is not detected for LS/PNO, which is attributed to the low area-specific resistance values. The results demonstrate that Pr2NiO4 and the composites are promising cathode materials for the apatite-type lanthanum silicate electrolyte for SOFC applications. © 2018 Wiley-VCH Verlag GmbH & Co. KGaA, Weinheim